2014
DOI: 10.1093/carcin/bgu153
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of a high-fat diet abrogates inhibitory effects of methylseleninic acid on spontaneous metastasis of Lewis lung carcinoma in mice

Abstract: We investigated the effect of dietary supplementation with selenium on spontaneous metastasis of Lewis lung carcinoma in mice fed a high-fat diet. Mice were fed a low-fat diet or that diet modified with 45% of calories from corn oil and supplemented with 0 or 2.5 mg selenium/4029 kcal as methylseleninic acid. After 6 weeks, mice were each injected 2.5 × 10 5 Lewis lung carcinoma cells subcutaneously. The resulting primary tumor was removed surgically 10 days later; the experiment was terminated after an additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…The expression of the adipokine PAI-1 is elevated in obese subjects [14], [15], and plasma levels of PAI-1 are elevated in mice fed obesigenic, high-fat diets [16], [17]. We reported that a high-fat diet enhances the malignant spread of Lewis lung carcinoma (LLC) in mice and this enhancement is accompanied by increases in plasma concentrations of PAI-1 [18], [19]. We hypothesized that PAI-1 participates in the spread of LLC and that the pro-metastatic effect of a high-fat feeding involves the up-regulation of PAI-1.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the adipokine PAI-1 is elevated in obese subjects [14], [15], and plasma levels of PAI-1 are elevated in mice fed obesigenic, high-fat diets [16], [17]. We reported that a high-fat diet enhances the malignant spread of Lewis lung carcinoma (LLC) in mice and this enhancement is accompanied by increases in plasma concentrations of PAI-1 [18], [19]. We hypothesized that PAI-1 participates in the spread of LLC and that the pro-metastatic effect of a high-fat feeding involves the up-regulation of PAI-1.…”
Section: Introductionmentioning
confidence: 99%
“…The status of nutritional essentiality was extended to humans in the 1980s when very low blood Se levels were associated with an endemic heart disease in parts of China [ 5 ] and Se supplementation was found to be preventive [ 6 ]. Starting in the 1960s, Se was shown to have anti-tumorigenic capabilities in a variety of animal models of both primary (see review [ 7 ]) and secondary tumors [ 8 , 9 ]. Those studies ultimately led to several human clinical trials that have shown cancer risk reduction for subjects of low to moderate Se status [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], but not for subjects of relatively high Se status, e.g., with plasma Se concentrations >120 ng/mL [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We showed that non-cytotoxic oxidant-induced damage sensitizes prostate cancer cell populations to apoptosis triggered by methylseleninic acid (MSA), a proximal precursor of methylselenol [14]. Methylselenol production is thought to play an important role in the anti-tumorigenic activity of dietary selenium [10,15]. Taken together, our results point to a new way in which selenium might render an aging prostate under oxidative attack more resistant to cancer.…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, careful evaluation of the relationship between selenium status and cancer risk suggests that the anticancer benefit of selenium supplementation in humans and animals cannot be explained simply by antioxidant protection, because it occurs at selenium levels at which selenium-dependent antioxidant enzymes are already maximized [3,[5][6][7][8]. More than ever before, investigators are motivated to explore new mechanisms of selenium anti-carcinogenesis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%